Efforts To Promote Exclusive Breastfeeding Education For Stunting Prevention Through Booklet Media For Third Trimester Pregnant - Dhita Kris Prasetyanti; Anis Nikmatul Nikmah; Rahma Kusuma Dewi; Hilda Oktafia Sukmawati (Journal of Global Research in Public Health, 2023)
Stunting is malnutrition that occurs over a long period of time, resulting in impaired growth of children's height shorter than their age standard. One of the prevention of stunting is by providing exclusive breastfeeding to infants. Exclusive breastfeeding helps adequate nutritional intake so as to minimize the risk of stunting in children. The purpose of this study is to determine the promotional efforts of exclusive breastfeeding education for stunting prevention in third trimester pregnant women in the Sukorame Health Center Working Area of Kediri City in 2023.Type of pre-experimental research type one group pre post test design, the population in this study is all third trimester pregnant women of East Nusa Tenggara Province, as many as 32 third trimester pregnant women in the Sukorame Health Center Working Area of Kediri City, with a sample of 16 third trimester pregnant women using purposive sampling techniques.  Statistical test using wilcoxon.The results of statistical tests using Wilcoxon obtained that p = 0.000 with a confidence level of 95% (α = 0.05) can be said if the value of ρ < α H0 is rejected and H1 is accepted, meaning that there is an influence on exclusive breastfeeding education promotion efforts for stunting prevention in third trimester pregnant in the Sukorame Health Center Working Area of Kediri City in 2023.It is expected that respondents can use booklet media to read in order to increase knowledge and provide information about the importance of exclusive breastfeeding for stunting prevention.